Soil and groundwater contamination by crude oil spillage: A review and implications for remediation projects in Nigeria - Adeniran, Margaret A.; Oladunjoye, Michael A.; Doro, Kennedy O. (Frontiers in Environmental Science, 2023)
Management of soil and groundwater resources has been recognized as essential to meeting the sustainable development goals of Agenda 2063 of the African Union. As Africa's fastest-growing population with over 200 million people, Nigeria is responsible for leading the continent's environmental sustainability goal. Nigeria has seen a sizable number of crude oil spillages that have contaminated its soils and groundwater resources, and several of these contaminated sites are yet to be cleaned up. There needs to be more scientific data to design an effective cleanup and to manage the soil and groundwater resources effectively. So far, the only extensive crude oil-contaminated site remediation project documented is on the Ogoni Land in the Niger Delta region of Nigeria. However, this project resulted in less effective, albeit temporary, cleanup solutions. This review presents a state-of-the-art synthesis of research on soil and groundwater contamination by crude oil. It includes sections on processes, measurements, predictions, and management, as well as an analysis of the state and challenges in Nigeria. In-depth field, laboratory, and computer models for crude oil contamination investigation have been developed with over 60 years of significant research. However, studies and case projects in Nigeria have relied on point sampling to determine the concentration of crude oil contaminants in soil and groundwater. This method offers limited information on the solute concentration and hydraulic distribution, which regulates pollutant mobility within the subsurface. The absence of baseline and high-resolution subsurface characterization data has also resulted in a need for more process-based knowledge to direct the development of site-specific remediation strategies. As a result, it is challenging to design a conceptual model that is detailed enough to help with predictions of the flow dynamics of crude oil contaminants in the unsaturated and saturated zones. It is anticipated that this review will stimulate further multidisciplinary research through site evaluation and monitoring to give reliable information that can be used to develop appropriate model-based remediation solutions.